Vargas and Brazil : new perspectives - Hentschke, Jens R. (Studies of the Americas., 2006)
More than seventy-five years after Getúlio Vargas's 1930 'Revolution' and more than half a century after his suicide, politicians, scholars and the Brazilian public still debate whether his era has actually come to an end. Yet, as Brazil's leading news magazine Veja emphasized in August 2004, Vargas's enigma will not be deciphered through uncritical studies and hagiographic novels, but through serious scholarly analyses. Vargas and Brazil: New Perspectives unites scholars from Brazil, the U.S. and Europe, who draw on a close re-reading of the literature, hitherto unavailable or unused sources, and a wide array of methodologies, to shed new light on the political changes and cultural representations of Vargas's regimes, thereby exploring why he meant so many different things to different people.